Clinical characteristics and recurrence predictors of sinonasal inverted papilloma: a retrospective cohort study - Li, XiangHua; Wang, DongFei; Yin, DeTao (Frontiers in Oncology, 2025)
ObjectiveTo investigate the clinical characteristics and predictors of postoperative recurrence in sinonasal inverted papilloma (SNIP).MethodsA retrospective cohort study of 53 SNIP patients treated at Zhengzhou University Hospital (2019–2023) was conducted. Patients were stratified into primary (n=34) and recurrent (n=19) cohorts. Clinical variables were analyzed using univariate and multivariate logistic regression.ResultsSmoking (OR=10.08, 95% CI=1.32–77.15), prior surgery (OR=17.26, 95% CI=2.69–110.76), and ipsilateral involvement (OR=7.79, 95% CI=1.05–57.99) emerged as independent recurrence predictors (P<0.05). Krouse staging (T3 vs. T1–T2) showed no significant association (P=0.198).ConclusionComprehensive evaluation of smoking history, surgical history, and lesion laterality is critical for recurrence risk stratification in SNIP management.